Sight-Translation Strategies and Quality. Part 2. The Impact of Directionality - Леонід Черноватий; Мартін Дйовчош; Наталя Ковальчук (Психолінгвістика)
Aim. The aim of this second part of the psycholinguistic research in the language pair Slovak-English is to determine the influence of directionality on the generation of the target text (TT) and its delivery by comparing the sight translation (SiT) of student interpreters from their native language (NL) into a foreign language (FL) and vice versa.